2004
DOI: 10.1590/s0103-84782004000100031
|View full text |Cite
|
Sign up to set email alerts
|

Soroprevalência de Borrelia burgdorferi latu sensu associada à presença de carrapatos em cães de áreas rurais do Estado do Rio de Janeiro, Brasil

Abstract: RESUMO Pesquisou-se a presença de anticorpos contra

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
1
1
4
Order By: Relevance
“…However, since 80% dogs' sera also demonstrated antibodies against p100 by WB (Table 1), an antigen for which no cross-reactivity has been reported, the antibodies detected here are likely a result of Borrelia infection. In addition, the present study corroborates previous studies (O'DWYER et al, 2004) in which no association was established between seropositivity to Borrelia spp. and age, gender, or presence of ticks in dogs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, since 80% dogs' sera also demonstrated antibodies against p100 by WB (Table 1), an antigen for which no cross-reactivity has been reported, the antibodies detected here are likely a result of Borrelia infection. In addition, the present study corroborates previous studies (O'DWYER et al, 2004) in which no association was established between seropositivity to Borrelia spp. and age, gender, or presence of ticks in dogs.…”
Section: Discussionsupporting
confidence: 92%
“…Antibody seropositivity to Borrelia spp. was found by WB in 18% of dogs in the present study, which is a higher prevalence than has been reported previously in tick endemic areas (JOPPERT et al, 2001;O'DWYER et al, 2004). Previous studies have shown cross-reactivity with antigens of other spirochetes, such as Leptospira antigens p41 and OspC (BRUCKBAUER et al, 1992;LESCHNIK et al, 2010), and it is important to note the possibility that dog sera in this study (untested for anti-Leptospira antibodies) may have tested positive by WB as result of cross-reactivity.…”
Section: Discussioncontrasting
confidence: 46%
“…Também não houve diferença significativa (P < 0,05) em relação à função desempenhada pelos animais. No presente estudo, não foi observada diferença significativa entre as freqüencias de animais soropositivos dos diferentes municípios e o resultado corrobora com os encontrados em outras espécies de animais domésticos no Brasil, como bovinos (Fonseca et al 1996) e caninos (O'Dwyer et al 2004). Resultados semelhantes foram reportados nos Estados Unidos da América, onde foram observadas soropositividade que variavam entre 12 e 75% em eqüinos sem sintomatologia clínica para borreliose de Lyme (Bernard et al 1990, Cohen et al 1988, Cohen et al 1992, Marcus et al 1985, Parker & White 1992.…”
Section: Resultsunclassified
“…Palácios et al (1999) No presente trabalho não houve diferença significativa entre a distribuição da prevalência de anticorpos anti-B.burgdorferi quanto a raças e sexos. Estes resultados estão de acordo com os observados por Salles et al 2002, O'dwyer et al 2004e Madureira et al 2007. Marcus et al (1985) observaram que nos EUA a freqüência de B. burgdorferi em eqüinos foi maior em áreas endêmicas que em áreas não endêmicas com soropositividade de 24% e 2%, respectivamente, não havendo diferença significativa entre raças e sexo.…”
Section: Resultsunclassified
“…The prevalence of antiBorrelia spp. antibodies in dogs is high in Brazil, varying from 9,0% to 83.9%, according to previous studies in different regions of the country (ALVES et al, 2004;CORREIA et al, 2012;JOPPERT et al, 2001;O'DWYER et al, 2004;SOARES et al, 2000). All these studies showed a close relationship between the ticks' infestation and high antibody rates against Lyme spirochetes.…”
Section: Introductionmentioning
confidence: 76%